EXPLORING TEACHER–STUDENT TALK IN ENGLISH FOR YOUNG LEARNERS (EYL) LED BY A GEN Z TEACHER: A FIACS-BASED CASE STUDY IN INDONESIA - Kurniawati, Arienta Eka; Hamamah, Hamamah; Muttaqin, Syariful (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2025)
Effective classroom interaction significantly contributes to successful English language learning among young learners. Despite extensive research on classroom interactions, the impact of Generation Z (Gen Z) teachers’ distinct communication traits remains underexplored, particularly within the Indonesian context. Drawing from social constructivism and digital pedagogy frameworks, this study addresses this gap by focusing on verbal interactions in an EYL setting in Indonesia. The research aims to explore how a Gen Z teacher’s communication style influences classroom interaction patterns and what pedagogical implications arise for student engagement, autonomy, and emotional development. A qualitative case study design was employed, involving one Gen Z teacher and 28 third-grade students at a private primary school in Indonesia. Data were collected over three 55-minute sessions using video recordings and coded through Flanders’ Interaction Analysis Categories System (FIACS). Reliability procedures and ethical consent were ensured prior to data collection. Findings show that direct talk such as asking questions (56.8%) and giving directions (41.5%), is more prevalent in Gen Z teacher interactions than indirect talk, like using student ideas (14%) and offering praise (15.11%). The emphasis on directive and questioning approaches limited the potential for fostering student autonomy and collaborative dialogue. Student responses were frequent (66.3%), indicating active engagement, yet minimal student-initiated talk suggests limited learner autonomy. The study suggests a need for professional development that encourages Gen Z teachers to balance directive communication with emotional support and digital integration. Enhancing these communicative strategies could improve student engagement, autonomy, and collaborative learning in EYL settings.